The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00705-018-3807-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of Interleukin-17F gene polymorphisms with susceptibility to severe enterovirus 71 infection in Chinese children

Abstract: Enterovirus 71 (EV71) is a single-strand RNA virus that causes hand, foot and mouth disease (HFMD) in infants and young children, leading to neurological complications with significant morbidity and mortality. Unfortunately, the pathogenesis of EV71 infection is not well understood. In this study, we investigated the IL-17F rs1889570 and rs4715290 gene polymorphisms in a Chinese Han population. Severe cases and cases with EV71 encephalitis had a significantly higher frequency of the rs1889570 T/T genotype and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…One study [41] demonstrated that the frequency of IL-17F-7488 C allele was significantly lower among the patients with EV71 encephalitis (5.2%) as compared to that without complications (15%, p = 0:006). However, the other study [42] showed that the serum IL-17F levels in rs1889570 T/T and T allele were significantly elevated in EV71 encephalitis cases. In a word, IL-17F gene polymorphisms are associated with the susceptibility to severe EV71 infection.…”
Section: Il-17 Familymentioning
confidence: 83%
“…One study [41] demonstrated that the frequency of IL-17F-7488 C allele was significantly lower among the patients with EV71 encephalitis (5.2%) as compared to that without complications (15%, p = 0:006). However, the other study [42] showed that the serum IL-17F levels in rs1889570 T/T and T allele were significantly elevated in EV71 encephalitis cases. In a word, IL-17F gene polymorphisms are associated with the susceptibility to severe EV71 infection.…”
Section: Il-17 Familymentioning
confidence: 83%
“…Tan et al 14 suggested that OAS2 rs739901 C/A gene polymorphism was related to EV‐A71 susceptibility, and A allele might be a risk factor for EV‐A71 infection. Similarly, the frequency of rs1889570 TT genotype and T allele in severe cases and EV‐A71 encephalitis cases were significantly higher and when compared with CC genotype, the serum IL‐17F levels of TT and CT genotype were also significantly higher 15 …”
Section: Discussionmentioning
confidence: 91%
“…Similarly, the frequency of rs1889570 TT genotype and T allele in severe cases and EV-A71 encephalitis cases were significantly higher and when compared with CC genotype, the serum IL-17F levels of TT and CT genotype were also significantly higher. 15 This evi- and plays a key role in the innate immune system. 17 Studies have…”
Section: Discussionmentioning
confidence: 99%
“…The inflammation cytokine IL17F is involved in innate and adaptive immune responses. Previous studies have indicated that IL17F is associated with a variety of inflammatory diseases, such as immune thrombocytopenia, severe enterovirus infection and aphthous stomatitis 7‐9 . Vrgoc et al 10 found that the T allele of rs763780 in IF17F was associated with a lower risk for developing HOA, whereas the C allele was associated with susceptibility to HOA Specifically, the genotype T/T of IF17F was associated with protection against HOA, but the genotype T/C was associated with a higher risk of acquiring HOA in a Croatian population.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that IL17F is associated with a variety of inflammatory diseases, such as immune thrombocytopenia, severe enterovirus infection and aphthous stomatitis. [7][8][9] Vrgoc et al 10 found that the T allele of rs763780 in IF17F was associated with a lower risk for developing HOA, whereas the C allele was associated with susceptibility to HOA Specifically, the genotype T/T of IF17F was associated with protection against HOA, but the genotype T/C was associated with a higher risk of acquiring HOA in a Croatian population. Most recently, a genetic epidemiology study of HOA found that the IL17A-IL17F haplotype (rs2275913-rs763780-rs1889570) G-C-A confers predisposition to HOA, and the IL17A-IL17F haplotype (rs2275913-rs763780) G-T is associated with protection from HOA in a Croatian population.…”
mentioning
confidence: 99%